A multidisciplinary treatment for encopresis in children with developmental disabilities. Issue 2 (17th February 2017) - Call, Nathan A.; Mevers, Joanna Lomas; McElhanon, Barbara O.; Scheithauer, Mindy C.
Abstract : Achieving continence of one's bowel movements is a key step in development and failure to do so leads to many negative consequences. Treatments for encopresis appearing in the literature have employed behavioral strategies; medications such as suppositories, laxatives, or enemas; and in some studies a combination of these approaches. To date, attempts to extend successful treatments for encopresis in typically developing children to those with developmental disabilities have been limited. The current study included three participants diagnosed with developmental disabilities who had a history of encopresis. None of the participants had a continent bowel movement under baseline conditions. Continent bowel movements increased during treatment that included the addition of suppositories to elicit continent bowel movements. Two participants began having independent continent bowel movements (i.e., without requiring suppositories) and medication was successfully faded out for the remaining participant. Treatment took between 13 and 21 days.